A switching formation strategy for obstacle avoidance of a multi-robot system based on robot priority model. (May 2015) - Dai, Yanyan; Kim, YoonGu; Wee, SungGil; Lee, DongHa; Lee, SukGyu
Abstract: This paper describes a switching formation strategy for multi-robots with velocity constraints to avoid and cross obstacles. In the strategy, a leader robot plans a safe path using the geometric obstacle avoidance control method (GOACM). By calculating new desired distances and bearing angles with the leader robot, the follower robots switch into a safe formation. With considering collision avoidance, a novel robot priority model, based on the desired distance and bearing angle between the leader and follower robots, is designed during the obstacle avoidance process. The adaptive tracking control algorithm guarantees that the trajectory and velocity tracking errors converge to zero. To demonstrate the validity of the proposed methods, simulation and experiment results present that multi-robots effectively form and switch formation avoiding obstacles without collisions. Abstract : Highlights: A switching formation strategy is proposed to avoid and cross obstacles. The switching formation strategy is under consideration of collision avoidance. A geometric obstacle avoidance control method is proposed for the leader robot. A novel robot priority model is cooperated with switching formation strategy. An adaptive algorithm is used for robot׳s motion control.